Can Flipped Classroom Increase Students' Learning Independence? - Selvita Eka Eviana Purba; Kristiani Kristiani; Khresna Bayu Sangka (Universitas Sebelas Maret, 2021)
Changes in education due to covid-19 are forcing teachers to use technology in learning. Teachers as facilitators must be able to use technology in innovative learning models so that they can increase learning independence. The purpose of this study is to find out how flipped classroom can increase students' learning independence. The research method used is literature study. Flipped classroom is a model that utilizes technology by reversing traditional teaching methods, where the teacher first provides learning material in the form of videos before going to class, so that classroom activities are used for active learning activities. The results show flipped classroom make teacher-student interactions better, improve learning outcomes, students can study learning materials anywhere and anytime and help students to understand learning before entering class so that students can learn independently without depending on the teacher according to their speed which in turn will increase student learning independence.